What crisis produces: Dangerous bodies, Ebola heroes and resistance in Sierra Leone - Luisa Enria (University of Bath, Centre for Development Studies (CDS), 2017)
This article explores the implications of framing an event as a 'crisis' through the case study of the Ebola epidemic in Sierra Leone, based on extensive ethnographic fieldwork during and after the outbreak. It traces how Ebola came to be declared an emergency, and the processes, which led to its definition as a 'threat to international peace and security'. Secondly, it highlights the consequences of this framing, as particular interpretations of the roots of the emergency drew a line between 'good' citizens willing to adapt and 'dangerous' ones needing to be contained. Finally, it turns to an ethnographic portrait of a traditional healer's attempts to navigate the crisis by appropriating the knowledge produced by the response apparatus. Considering how those at the receiving end of policy discourses strategically reposition themselves in relation to the narratives that frame them, can help us question the reductive dichotomy between adaptation to and resistance against interventions.
Keywords: 330; Ebola; Sierra Leone; emergency; knowledge production